ANALISIS PENGARUH KEPUASAN, KUALITAS, DAN EXPERIENTIAL MARKETING TERHADAP WORD OF MOUTH APLIKASI WHATSAPP PADA MAHASISWA FEB UMT - Hendi Eka Sumarga (Universitas Muhammadiyah Tangerang, 2017)
This study aims to analyze the effects of satisfaction, quality, andexperiential marketing on the creation of word of mouth in theapplication WhatsApp. This study uses three independent variables ofsatisfaction, quality, and experiential marketing with one dependentvariable ie word of mouth. The use of variables in this study is expectedto know how the process occurs and what are the factors driving thecreation of word of mouth in WhatsApp application. The sample of thisresearch is user of WhatsApp application from student of Faculty ofEconomics and Business of University of Muhammadiyah Tangerang.Samples were taken with non probability sampling technique. Dataanalysis of 160 respondents was done using Structural EquationModeling (SEM) as an analysis tool using LISREL 8.8 software. Based onthe results of data analysis, shows that: experiential marketing variableshave a positive influence and the greatest influence on word of mouthWhatsApp applications, satisfaction variable has a positive influence onword of mouth WhatsApp applications. The quality variable has theleast positive effect on word of mouth WhatsApp applications.